Strategi Nilai Perusahaan di Tengah Risiko Bisnis: Peran Moderasi Risiko Terhadap GCG, CSR, Kinerja Keuangan, dan Ukuran Perusahaan - Ningsih, Ningsih; Diah Lestari, Widyanti; Robin, Robin (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
The purpose of this study is to examine whether the role of Good Corporate Governance, Corporate Social Responsibility, Financial Performance, and company size has an impact on business assessment and risk, and whether this can be seen if the moderating variable is used as a link. The period used is from 2019 to 2023. The sample was taken from transportation and logistics companies listed on the Indonesia Stock Exchange using STATA software. Data processing used a quantitative approach, multiple linear regression analysis, and moderation regression. The results indicate that company size has no significant impact, while GCG, CSR, and KK have a significant positive impact. Overall, the impact of these four variables is significant, with an R² value of 44.67%. When business risk is added as a moderating variable, the adjusted R² value increases to 60.74%, which means that business risk strengthens the existing model. Business risk proves that the relationship between CGC and company value produces negative moderation, while CSR and company value produce positive moderation.